2016
DOI: 10.1016/j.drugalcdep.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of alcohol consumption and health-related quality of life in older adults

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:Drug and Alcohol Dependence 159 (2016) Conclusions:The small association between alcohol consumption and better physical HRQOL found at baseline was not apparent after a few years of follow-up. Medical advice on alcohol consumption cannot be grounded on its effects on HRQOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
5
24
3
Order By: Relevance
“…Regarding the association between smoking and HRQoL, the findings in this study were not in agreement with inverse association [108][109][110][111][112]. Regarding the association between alcohol drinking and HRQoL, the findings in this study were in line with positive association between alcohol drinking and physical HRQoL [113][114], positive association between alcohol consumption and higher HRQoL in female [115]. The findings in this study were not in line with negative associations [116][117][118][119] in the early studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Regarding the association between smoking and HRQoL, the findings in this study were not in agreement with inverse association [108][109][110][111][112]. Regarding the association between alcohol drinking and HRQoL, the findings in this study were in line with positive association between alcohol drinking and physical HRQoL [113][114], positive association between alcohol consumption and higher HRQoL in female [115]. The findings in this study were not in line with negative associations [116][117][118][119] in the early studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Regarding the association between alcohol drinking and HRQoL, the findings in this study were in line with positive association between alcohol drinking and physical HRQoL [73], positive association between alcohol consumption and higher HRQoL in female [74]. The findings in this study were not in line with negative associations [75] in the early studies.…”
Section: Discussioncontrasting
confidence: 50%
“…Finally, sensible drinkers had a better HRQOL of the psychological domain compared to the hazardous drinkers. Studies showed that moderate to heavy drinkers had a lower HRQOL (mental health) than nondrinkers or occasionally drinkers [40,41]. Alcohol consumption can impair an individual's cognitive and altered consciousness.…”
Section: Discussionmentioning
confidence: 99%